Mechanism of 17β-estradiol stimulated integration of human mesenchymal stem cells in heart tissue. (August 2019) - Mihai, Maria Cristina; Popa, Mirel Adrian; Suica, Viorel Iulian; Antohe, Felicia; Jackson, Edwin K.; Simionescu, Maya; Dubey, Raghvendra K.
Abstract: Scarcity of gender specific donor hearts highlights the importance of mesenchymal stem cells (MSCs) as a therapeutic tool for heart repair. However, inefficient incorporation, retention, and activity of MSCs in cardiac tissue remain an obstacle. Since surges in follicular estradiol (E2; μmolar-range) trigger tissue remodeling (e.g. ovulation) and E2 exerts beneficial actions on the cardiovascular system, we hypothesized that E2 may promote/improve MSC-mediated cardiac repair processes. Using Wharton's jelly (WJ)-derived MSCs we assessed the effects of E2 on MSC proliferation, directed migration, and engraftment in murine heart slices (using xCELLigence real-time cell-impedance system, DNA quantification, and microscopy) and on MSC-induced angiogenesis in vivo (matrigel plug assay). Protein expression was assessed by Western blotting, ELISA/Luminex, and proteomic analysis; whereas mRNA expression was assessed by qRT-PCR. MSCs expressed estrogen receptors (ERs) -alpha and -beta. E2 promoted MSC proliferation and up-regulated mRNA and protein expression of ER-alpha, ER-beta, extracellular matrix metalloproteinase inducer (EMMPRIN), and matrix metalloproteinase (MMP) -9, yet down-regulated MMP-2 expression. Moreover, E2 up-regulated expression of vascular endothelial growth factor (VEGF)-A, VEGFR-2, vascular cell adhesion protein-1 (VCAM-1), and angiogenin (ANG) and stimulated nitric oxide (NO) production via ER. Proteomic analysis of MSCs showed that E2 up-regulated 47 proteins, down-regulated 7 proteins, and increased the expression of key biochemical components/pathways involved in tissue repair. In MSCs co-cultured with murine heart-slices, E2 significantly induced MSC migration in an ER-alpha-dependent fashion and significantly increased the secretion of MMP-2, MMP-9, ANG, and VEGF. In an in vivo matrigel assay, E2-treated MSCs increased angiogenesis and hemoglobin content. In conclusion, E2-treatment increases the incorporation of MSCs in heart slices and promotes MSC-induced angiogenesis. These beneficial effects are mediated via increases in molecules/pathways involved in tissue remodeling and angiogenesis. We speculate that E2 may enhance MSC ability to repair/regenerate cardiac tissue. Graphical abstract: Unlabelled Image Highlights: Estradiol (E2) induces proliferation and migration of adult mesenchymal stem cells (MSCs). Priming of human MSCs with E2 enhances their migration to and engraftment in cardiac slices, as well as angiogenesis. Via ERs, E2 improves MSC engraftment by upregulating key genes/proteins/pathways that modulate tissue remodeling/repair. Using E2 primed adult MSCs may be a simple therapeutic approach to enhance MSC mediated heart repair and improve function.